Sistema de controle Fuzzy para veículo elétrico de duas rodas - Anjos, Iuri Miranda dos (2017)
In the last decade, two-wheeled electric vehicles have been built for applications in human mobility, mobile robotic applications, industrial conveyors and robots for home applications. This work presents the design and development of a twowheel electric vehicle controlled by a system based on a Fuzzy controller. A prototype was built with two DC motors coupled to the wheels of the vehicle, so the tires will be independently controlled but synchronized with the desired movement. The control system is feedback with the angular speeds of the motors, the driver's action on the vehicle's handlebar determines the reference speed and steering. The angular speeds of the motors and the angle of inclination of the handlebar are processed by a microcontroller. An electronic instrumentation system is applied to read the input variables and send the results to the output as a PWM signal to feed the motors. Sensors of rotary incremental encoder and MEMS gyro are used to measure the angular velocity and angle of inclination of the handlebar respectively. The power unit, too, was developed as an interface for the application of the PWM signal in the motors. A microcontrolled system was used for the purpose of managing the desired speed and direction of the vehicle. At the end, the driver's response to different pitch and yaw angles is presented, indicating by graphs the value of the angular velocities in RPM imposed by the controller. At the end, the control response is presented for different pitch and yaw angles, indicating by graphs the value of the angular velocities in RPM imposed by the controller.